Editorial: Consequences of the COVID-19 Pandemic on Care for Neurological Conditions - Matias Guiu, Jordi A. (2021)
The coronavirus disease 2019 (COVID-19) pandemic has caused a wide range of unprecedentedconsequences, including social, economic, and health disruptions. From the point of view ofhealthcare assistance, COVID-19 has deeply impacted usual practice at all levels since the beginningof 2020. In this setting, neurological assistance has adapted to the circumstances of the pandemic. Infact, because COVID-19 involves neurological symptoms, affected patients require the attention ofneurologists, and the high demand for clinical care entailed the recruitment ofmany neurologists tofrontline assistance (1). In addition, the pandemic has impacted the management of patients withneurological disorders, with changes in the management of relapses, usual follow-up, diagnosticprocedures, implementation or generalization of telemedicine, etc. Lockdown and social isolationwere also very harmful in patients with neurological disorders (2). Furthermore, the treatment ofneurological emergencies, such as stroke, was also compromised because of resource re-allocationduring the emergency, and the fear of patients to attend the hospital.The neurological community needed to share experiences about how to face this globalchallenge. Accordingly, this Research Topic was launched in April 2020 to address these issues.Over 117 manuscripts were submitted, and 76 papers have been published, including originals,reviews, and case reports. Studies have covered the main areas of neurological care, includinggeneral neurological care, stroke, epilepsy, multiple sclerosis, movement disorders, cognitiveneurology, neuromuscular disorders, headache, and neuropediatrics